Obtaining plant Miscanthus sacchariflorus (Maxim.) Hack and Miscanthus sinensis Andersson in vitro culture by indirect morphogenesis - С. М. Гонтаренко; С. О. Лашук (Plant Varieties Studying and Protection)
Purpose. To obtain Miscanthus sacchariflorus (Maxim.) Hack and Miscanthus sinensis Andersson in vitro culture by indirect morphogenesis.